Changes in visual quality with soft contact lenses after the instillation of hyaluronic acid eye drops. Issue 6 (December 2021) - Carpena-Torres, Carlos; Pastrana, Cristina; Rodríguez-Pomar, Candela; Serramito, María; Batres, Laura; Carracedo, Gonzalo
Highlights: During Ocufilcon D contact lens wear, the instillation of 0.1% and 0.2% hyaluronic acid showed an improvement in the visual quality. During Somofilcon A contact lens wear, the instillation of 0.3% hyaluronic acid showed a deterioration in the visual quality. Depending on the properties of contact lens materials, the instillation of hyaluronic acid could have a different effect on visual quality. Abstract: Purpose: To evaluate the changes in visual function and anterior surface aberrations during soft contact lens (SCL) wear after the instillation of hyaluronic acid (HA) eye drops with different viscosity. Methods: A prospective, randomized, and participant-masked study was performed. Twenty healthy participants (25.4 ± 2.6 years) were evaluated. Hydrogel (Ocufilcon D) and silicone-hydrogel (Somofilcon A) SCL were randomly assigned to both eyes of the same participant. Visual function in terms of high- and low-contrast corrected distance visual acuity (CDVA) and anterior contact lens surface aberrations (RMS HOA) were measured before and after the instillation, at different times, of different eye drops: saline (control) and 0.1%, 0.2%, and 0.3% HA. Results: Compared with the saline solution, during hydrogel SCL wear, there was an improvement (P < 0.05) in high-contrast CDVA after 3 and 10 min with 0.1% HA, and after 5 and 20 min with 0.2% HA. During silicone-hydrogel SCL wear, there was a deterioration (P < 0.05) in high-contrast CDVA after 1 and 30 min with 0.3% HA. Additionally, during silicone-hydrogel SCL wear, there was also a deterioration (P < 0.05) in low-contrast CDVA after 5 and 20 min with 0.3% HA. In terms of RMS HOA, there were no clinically relevant changes with both SCL. Conclusions: The instillation of HA eye drops could have a different effect on visual quality depending on their concentration of HA, the contact lens material, its surface ionicity, or other physicochemical properties that should be studied in future studies.